The analisis of interaction monosaccharides with aminoacides in food row by quantum-chemical methods - Popova, Inna; Mayboroda, Elena; Simurova, Natalia; Karmashov, Oleksandr (My University, 2020)
The object of research is the products of hydrolysis of the polysaccharide inulin (glucose, fructose) of plant raw materials used for the production of food products for health-improving and prophylactic purposes. The search for optimal conditions for the transformation of polysaccharides in the processes of hydrolytic cleavage into fructose-oligosaccharide products requires a thorough study of both the chemical composition of the raw material and the interaction between the components. This affects both the stability of the initial, intermediate and final products of the hydrolysis of the polysaccharide, and its release from plant materials and the further course of its fragmentation. Literature data indicate that the chemical composition of carbohydrate-containing plant materials, in particular the content of mineral components, has not yet been fully studied and requires additional research and refinement. After all, macro- and microelements in its composition are not only important nutrients, but can also take an active part in the transformation of organic components through complexation at intermediate stages of these processes. In addition, the question of the possible interaction of organic compounds in the composition of food raw materials, in particular biopolymers, which make up a significant part of the mass – carbohydrates and protein compounds, also requires attention. Such interaction under normal conditions has practically not been studied, but it can affect the course of technological processes of processing. The study of intermolecular interac-tions occurring in complex natural systems is often complicated either by the absence of direct (selective) physical and physicochemical research methods, or by the multicomponent chemical composition of the system, or by the complexity of the objects (substances) of the study themselves. This is especially true for natural substances of a polymeric nature – proteins, peptides, poly- and oligosaccharides. Therefore, the work paid special attention to the study of the interaction of these components. The spatial structure of inulin molecules, oligosaccharides and elementary units of these polymers has been investigated using quantum chemical modeling. The distribution of ef-fective charges on carbohydrate atoms is calculated; it directly affects their reactivity. And also quantum-chemical models of the interaction of protein substances of plant materials with carbohydrates in vacuum and in aqueous solutions are created, depending on their dilution.
Keywords: polysaccharide hydrolysis; oligosaccharides; amino acids; quantum-chemical modeling; effective charges; sweeteners; chemical bonds; гідроліз полісахаридів; олігосахариди; амінокислоти; квантово-хімічне моделювання; ефективні заряди; підсолоджувачі; хімічні зв’язки; кафедра харчової хімії